Analytical Equations for Predicting Concentration and Mass Flux from Composite Liners. Issue 6 (1st January 2001) - Foose, G.J.; Benson, C.H.; Edil, T.B.
Abstract : Composite liners, consisting of a geomembrane overlying a soil liner, are often required as bottom liners for waste containment systems. In many applications, regulations prescribe the type of liner that must be installed. However, regulations often have provisions that permit an alternative liner design, provided that the alternative liner is equivalent to, or as effective as, the prescriptive liner. The current approach for demonstrating equivalency is based on comparing leakage rates for the alternative and prescriptive liners. This approach is too simplistic because leakage rate is not always indicative of the mass of contaminants discharged from the liner. In this paper, practical equations are presented for predicting the discharge of contaminants from composite liners and for designing alternative liners. The equations can be implemented using hand-held calculators or computer spreadsheet applications. Some of these equations are shown to provide predictions of mass flux and contaminant breakthrough that are similar to predictions made with more complex one- and three-dimensional numerical models for composite liners having perfect contact, circular defects, a constant source concentration, and relatively simple boundary conditions.